Prevalence of Lumbosacral Transitional Vertebrae among Patients Presenting with Low Back Pain at a Tertiary Care Hospital - Thapa, Puja; Rayamajhi, Mallika; Amatya, Bishwo Ram; Shah, Aashish; Pant, Sujit; Kunwar, Bhuban Raj (Medical Journal of Shree Birendra Hospital, 2025)
Introduction: Low back pain (LBP) is a widespread health issue affecting millions globally and is projected to increase due to population growth and ageing. Lumbosacral transitional vertebra (LSTV) is a congenital anomaly implicated in spinal pathology and pain, yet its clinical significance remains debated. This study aims to determine the prevalence of LSTV among patients with LBP in a tertiary hospital setting and classify it using Castellvi’s classification. Methods: This was a descriptive cross-sectional observational study conducted after an ethical clearance from the Institutional Review Committee. The study was conducted from April to June 2024. Anteroposterior lumbosacral spine radiographs of patients presenting with LBP at the pain clinic of Shree Birendra Hospital were analyzed. X-rays were evaluated for LSTV presence and classified according to Castellvi’s criteria. Data were analyzed using IBM SPSS version 22. Results: A total of 150 patients were included in the study with a mean age of 46.53 ± 14.78 years. The prevalence of LSTV was 29 (19.3%) in the study. Type IIa 18 (62%) was the most common subtype, followed by types IIIb 8 (27.5%) and Ia 3 (10.3%). Sacralization was more prevalent 20 (68.9%) compared to lumbarization 9 (31.1%). The prevalence of LSTV was higher in females 23 (79.3%) than in males 6 (20.6%). Conclusions: The prevalence of LSTV among patients with LBP was higher than in the general population, with Type II being the most frequent.